Estimation of Electric Energy Required by Electric Vehicles based on Travelled Distances in a Residential Zone - Mendoza, Cristian C.; Quintero, Adriana M.; Santamaria, Francisco; Alarcón, Jorge A. (TECCIENCIA, 2016)
This paper presents a methodology to estimate electric energy required by electric vehicles, taking into account driving habits and mobility statistics of private vehicles. Initially, a probability function of accumulated distances that an electric vehicle travels on a normal operation day is developed based on mobility patterns (travelled distances, number of trips, etc.). The obtained information is used to generate probability distributions for travelled distances by vehicles and for energy required by a vehicle after its daily operation. Probability distributions allow assigning to each vehicle a travelled distance and a required energy with a behavior based on real data. From obtained functions, energy required by each electric vehicle is analyzed, which is essential information to evaluate the effect of massive connection to the power grid. In this way, under the proposed methodology it is provided a tool that could predict the amount of energy required by a given quantity of electric vehicles that are connected to the grid. Finally, the proposed methodology was validated in Bogota, Colombia determining the probability distribution of the energy consumed per vehicle.